2013
DOI: 10.1186/2041-7136-3-22
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring changes in pastoral resources in eastern Sudan: A synthesis of remote sensing and local knowledge

Abstract: The pastoral resources in eastern Sudan are changing under the combined impact of increasing anthropogenic activities such as clearance of natural vegetation and the effect of state policies that favour crop farming against pastoralism. Remotely sensed data are used to detect spatial and temporal changes from 1979 to 2009 in the land use/land cover (LULC) across three study sites. Areas of natural vegetation have been reduced from 26.1% in 1979 to 12.6% in 1999 and further to 9.4% in 2007. The majority of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…As the figure illustrates, this change causes a noticeable downturn in the agent's performance, with access to resources becoming both more limited (sample mean: 0.907) and more unreliable (standard deviation: 0.053). This result implies that extensive ecological knowledge and its inheritance constitute a major component of pastoral adaptability, again corroborating the wide array of empirical observations found in the literature (Oba & Kaitira, 2006;Sato, 1980;Schareika, 2003;Sulieman & Ahmed, 2013).…”
Section: One Nomad Modelsupporting
confidence: 69%
See 1 more Smart Citation
“…As the figure illustrates, this change causes a noticeable downturn in the agent's performance, with access to resources becoming both more limited (sample mean: 0.907) and more unreliable (standard deviation: 0.053). This result implies that extensive ecological knowledge and its inheritance constitute a major component of pastoral adaptability, again corroborating the wide array of empirical observations found in the literature (Oba & Kaitira, 2006;Sato, 1980;Schareika, 2003;Sulieman & Ahmed, 2013).…”
Section: One Nomad Modelsupporting
confidence: 69%
“…These movements have long been the object of detailed description among anthropologists and geographers (e.g., Bassett, 1986;Niamir-Fuller, 1999;Sato, 1980;Stenning, 1957). In addition to these studies, there is now a growing body of research that extensively utilizes advanced technologies such as satellite imagery and GPS to track the movements of pastoralists and their livestock (Adriansen & Nielsen, 2005;Butt, 2010;Degteva & Nellemann, 2013;Ermon et al, 2015;Moritz et al, 2010;Pickup & Chewings, 1988;Sulieman & Ahmed, 2013;Turner & Hiernaux, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a growing body of literatures (Oba 1998;Angassa and Beyene 2003;Angassa and Oba 2008;Angassa et al 2012) have tried to inform policy-makers and development practitioners to recognize community's knowledge for sustainable management of their environment. Previous studies (Feye 2007;Mohammed 2004Mohammed , 2010Angassa et al 2012;Sulieman and Ahmed 2013) have also shown that communities' knowledge has a role to play in the advancement of scientific research and attainment of sustainable development goals.…”
Section: Introductionmentioning
confidence: 99%
“…Although Afar pastoralists were frequently affected by the impact of drought, those coping strategies adopted by the local communities are key in terms of communities' responses to ecological crisis that occurred in the study areas. Similarly, in the neighboring country in Sudan, pastoralists use indicators like rainfall pattern that has a significant role in the process of minimizing the damage caused by climate change (Sulieman and Ahmed 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the spotlight is community indigenous knowledge about their rangeland and the relationships between pastoralists' perception of climate change and the existing metrological-based empirical data aiming at understanding the perception of pastoralists within differently intervened types of pastoral districts within relatively similar ecological conditions and its correlation with the actual climate change. Several studies with regard to herders' perceptions on climate change issues have been reported in Sudan (Sulieman and Ahmed 2013), Tanzania (Mwenda and Laswai 2013), and other parts of the world (Hou et al 2012;Li et al 2014). However, little has been done in evaluating community-based knowledge at a household level about the condition of their rangelands, existing coping strategies adopted by these communities to overcome the impacts of climate change and variability on pastoralists' livelihood as well as spotting the socio-economic factors affecting their coping capacity in Amibara and Gewane districts of Afar region, North-East Ethiopia.…”
Section: Introductionmentioning
confidence: 99%